Ground heat exchanger - CWIK, KRZYSZTOF (2016)
This invention relates to a ground heat exchanger utilizing the geothermal energy of the ground, comprising pipe conduits and channels mounted within a support structure. According to the invention, a layer of air-permeable materials is formed on the virgin soil (1), horizontally and/or at a small inclination angle relative to the horizontal direction, creating a circulation channel (9) of the exchanger, the channel being confined by a support slab (14) with spacer elements (11) coupled with a construction net (8) seated onto a stabilizing net (7), the whole structure being covered by an insulating layer (19). Furthermore, the heat exchanger is equipped with a collector of the process air having an appropriate shape.